Proceedings of the 5th Annual ACM Web Science Conference 2013
DOI: 10.1145/2464464.2464499
|View full text |Cite
|
Sign up to set email alerts
|

Detecting cyberbullying

Abstract: In this paper we describe a close analysis of the language used in cyberbullying. We take as our corpus a collection of posts from Formspring.me. Formspring.me is a social networking site where users can ask questions of other users. It appeals primarily to teens and young adults and the cyberbullying content on the site is dense; between 7% and 14% of the posts we have analyzed contain cyberbullying content.The results presented in this article are two-fold. Our first experiments were designed to develop an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…According to the results of Wilcoxon signed rank test, it is found that there is a significant difference between males and females in terms of the frequency in using the foul words in their posts fig 2 illustrates Top ten frequently used foul words by female (circle) versus male (square). On the other hand the researchers in [12] pore in studying cyberbullying and cyber harassment. They used analyzing language to detect cyberbullying appeared in the texts at social networks or SMS.…”
Section: Technical Partmentioning
confidence: 99%
“…According to the results of Wilcoxon signed rank test, it is found that there is a significant difference between males and females in terms of the frequency in using the foul words in their posts fig 2 illustrates Top ten frequently used foul words by female (circle) versus male (square). On the other hand the researchers in [12] pore in studying cyberbullying and cyber harassment. They used analyzing language to detect cyberbullying appeared in the texts at social networks or SMS.…”
Section: Technical Partmentioning
confidence: 99%
“…The majority of the publications apply either lexicon [28,31] or machine learning approaches [14,29,30]. Lexicon approaches entirely rely on a lexicon containing offensive words typically used in hate speech.…”
Section: Approaches To Detect Hate Speechmentioning
confidence: 99%
“…However, their practical applicability is limited, especially in the context of online harassment detection as they achieve only reasonable to moderate classification performance [28]. As a consequence, they are often used to preselect potential offending messages to perform subsequent analyses [31].…”
Section: Approaches To Detect Hate Speechmentioning
confidence: 99%
See 2 more Smart Citations